Characteristics associated with organic food consumption during pregnancy; data from a large cohort of pregnant women in Norway - Roos Gun; Stigum Hein; Lieblein Geir; Haugen Margaretha; Brantsæter Anne; Torjusen Hanne; Holmboe-Ottesen Gerd; Meltzer Helle (BMC, 2010)
Abstract Background Little is known about the use of organic food during pregnancy. The aim of this study was to describe characteristics associated with the use of organic food among pregnant women participating in the Norwegian Mother and Child Cohort Study (MoBa). Methods The present study includes 63,561 women who during the years 2002-2007 answered two questionnaires, a general health questionnaire at gestational week 15 and a food frequency questionnaire at weeks 17-22. We used linear binomial regression with frequent versus rare use of organic food as outcome variable and characteristics of the respondent as independent variables. The outcome variable was derived from self-reported frequency of organic food use in six main food groups (milk/dairy, bread/cereal, eggs, vegetables, fruit and meat). Results Organic eggs and vegetables were the food items which were most frequently reported to be used "often" or "mostly". The proportion of women reporting frequent intake of organic food was 9.1% (n = 5754). This group included more women in the lower (<25 years) and higher (>40 years) age-groups, with normal or low body mass index, who were vegetarians, exercised regularly (3+times weekly), consumed alcohol and smoked cigarettes during pregnancy (p < 0.001 for all, except alcohol: p=0.044). Further, participants with frequent organic consumption included more women in the lower (≤12 years) or higher (17 years +) category of educational attainment, women who were students or had a partner being a student, who belonged to the lowest household income group (both respondent and her partner earned <300 000 NOK), who entered the study 2005-2007, and who lived in an urban area (p < 0.001 for all). Conclusions The socio-economic characteristics of pregnant Norwegian women with frequent organic consumption did not unambiguously follow those typically associated with better health, such as higher levels of education and income. Rather, lower household income, and both lowest and highest levels of education were associated with a higher prevalence of frequent organic consumption. The results indicate that personal and socio-economic characteristics are important covariates and need to be included in future studies of potential health outcomes related to organic food consumption during pregnancy.